Ultrahigh-strength wrought magnesium alloy and preparation method thereof
By adopting semi-continuous casting process and multi-stage process processing in magnesium alloys, the problem of insufficient mechanical properties of deformed magnesium alloys is solved, high strength and good elongation are achieved, and the performance of magnesium alloys in engineering applications is improved.
Patent Information
- Application Number
- CN202411944824.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-01
AI Technical Summary
In the prior art, the alloys prepared with deformation magnesium alloys have relatively poor room temperature mechanical properties, especially insufficient tensile strength and yield strength, which limits their widespread use in engineering applications.
The Mg-Gd-Y-Zn-Mn alloy is prepared by semi-continuous casting process, and the mechanical properties of the alloy are improved through double-stage high-temperature solution treatment, extrusion deformation and aging treatment.
Through the above process treatment, the tensile strength, yield strength and elongation of the alloy reached 528MPa, 294MPa and 10.5%, respectively, which significantly improved the comprehensive mechanical properties of the alloy.
Smart Images

Figure BDA0005213387230000081 
Figure HDA0005213387240000011 
Figure HDA0005213387240000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnesium alloy materials, and in particular to an ultra-high strength deformable magnesium alloy and a preparation method thereof. Background Art
[0002] Magnesium alloy is one of the lightest metal structural materials currently used in engineering applications. The density of pure magnesium is only 1.74g / cm 3 , which is about 2 / 3 of aluminum and 1 / 4 of iron. At the same time, magnesium alloy has become the most promising new structural material after steel and aluminum alloy due to its advantages of weight reduction, high specific strength and specific stiffness. Magnesium alloy is widely used in many fields such as automobile, aerospace, 3C, etc. due to its lightweight, excellent comprehensive mechanical properties, and abundant reserves in the earth's crust. However, its relatively low engineering strength has become one of the most important factors hindering its widespread application. Therefore, it is particularly important to prepare ultra-high strength magnesium alloy with excellent performance.
[0003] Deformed magnesium alloys are usually obtained by deforming cast magnesium alloys. Deformed magnesium alloys usually achieve significant performance improvements, among which the alloy composition and deformation process parameters will have a greater impact on the alloy structure and mechanical properties. Among the many magnesium alloys developed in recent years, Mg-RE alloys are undoubtedly the high-performance rare earth magnesium alloys that have been studied more in recent years. At the same time, adding Mn elements to magnesium alloys can not only serve as an effective grain refiner, but also effectively remove Fe and other inclusion impurities in the melt to further purify the melt and improve the alloy performance. At present, there are few reports on the preparation of deformed magnesium alloys with a tensile strength of >500MPa using semi-continuous casting technology. Therefore, it is of great significance to explore and develop an ultra-high strength deformed magnesium alloy and its preparation method. Summary of the invention
[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide an ultra-high strength deformable magnesium alloy and a preparation method thereof, so as to solve the problem that the room temperature mechanical properties of the deformable magnesium alloy prepared in the prior art are relatively poor.
[0005] To achieve the above object, the first aspect of the present invention adopts the following technical solution: a method for preparing an ultra-high strength deformable magnesium alloy, comprising the following steps:
[0006] A Mg-Gd-Y-Zn-Mn alloy is obtained by a semi-continuous casting process;
[0007] The Mg-Gd-Y-Zn-Mn alloy was subjected to a double-stage high-temperature solution treatment to obtain a sample, and the sample was water-cooled to room temperature;
[0008] The sample is subjected to extrusion deformation treatment to obtain an extruded rod, and the extruded rod is subjected to air cooling treatment to room temperature;
[0009] The extruded bars are subjected to aging treatment and then air-cooled to room temperature.
[0010] Further, the semi-continuous casting process specifically comprises the following steps:
[0011] Preheat the crucible: set the resistance furnace temperature to 550-600°C;
[0012] Furnace loading: first add pure magnesium ingots several times, and sprinkle a layer of RJ-6 flux on the surface after adding pure magnesium ingots each time;
[0013] Alloy composition homogenization treatment: raise the temperature of the resistance furnace to 770-790℃, scrape off the scum on the liquid surface, then add Mg-30Gd master alloy, Mg-5Mn master alloy, Mg-30Y master alloy and pure zinc ingot into the crucible, stir and sprinkle RJ-6 flux evenly, clean the scum on the bottom and surface of the pot after stirring, and let it settle for 5-10 minutes;
[0014] Refining: Insert the argon tube 80-100mm above the bottom of the crucible and pass argon in all directions, with a flow rate of 0.03-0.08MPa. Refine for 10-20min. After refining, scrape off the surface scum, sprinkle a layer of RJ-6 flux on it, and then perform high-temperature and low-temperature standing in turn;
[0015] Semi-continuous casting: Semi-continuous casting is carried out under the protection of sulfur hexafluoride and argon in a volume ratio of 1:5. After drying the inside of the crystallizer, lubricating oil is brushed on its inner wall, and the casting temperature is controlled to be 710-730°C, the water temperature is room temperature, the casting speed is 110-130mm / min, the water flow rate is 100-120L / min, and the water pressure is 0.15-0.25Mpa.
[0016] Furthermore, the high-temperature standing is standing at a temperature of 780 to 810° C. for 10 to 20 minutes; and the low-temperature standing is standing at a temperature of 670 to 700° C. for 10 to 20 minutes.
[0017] Furthermore, the refining is performed sequentially as primary refining and secondary refining; wherein:
[0018] The primary refining comprises: inserting an argon tube 80 to 100 mm above the bottom of the crucible and pulling it upward, adjusting the argon flow rate to 0.03 to 0.08 MPa in eight equal directions of the crucible diameter, refining for 5 to 10 minutes, and continuously and evenly spreading the refining agent on the wave crest during the refining process;
[0019] The secondary refining is as follows: argon is used for stirring for 5 to 10 minutes, the gas flow rate is 0.03 to 0.08 MPa, and the refining agent is continuously and evenly sprinkled on the wave crest during the refining process until the surface of the magnesium melt becomes mirror-like, and the refining is stopped;
[0020] The total amount of refining agent used in the primary refining and the secondary refining is 2-3% of the total amount of raw materials.
[0021] Furthermore, the refining agent includes RJ-6 flux and magnesium fluoride, wherein the mass ratio of RJ-6 flux to magnesium fluoride is 4:1.
[0022] Further, the two-stage high temperature solution treatment is specifically:
[0023] First, the solution is carried out at a solution temperature of 480-500°C for 6-10 hours, and then the temperature is raised to 520-540°C and the solution is carried out for 10-14 hours.
[0024] Furthermore, the extrusion temperature in the extrusion deformation process is 400-450° C., and the extrusion ratio is 14-16:1.
[0025] Furthermore, the aging temperature in the aging treatment is 190-210° C., and the aging time is 36-64 hours.
[0026] The second aspect of the present invention adopts the following technical solution: an ultra-high strength deformable magnesium alloy is prepared by the preparation method of the ultra-high strength deformable magnesium alloy described in the first aspect of the present invention.
[0027] Further, the components are calculated by mass percentage:
[0028] Gd 9.5%~10.5%;
[0029] Y 1.5%~2.5%;
[0030] Zn 1%~1.5%;
[0031] Mn 0.5%~0.8%;
[0032] The remainder is Mg and other irremovable impurity elements.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The present invention adds Mn element as a grain refiner in the magnesium alloy, and also plays an important role in melt purification; the casting method of the original alloy ingot adopts semi-continuous casting, which can obtain a faster cooling speed than traditional casting and further refine the grains; after two-stage solid solution, extrusion deformation and aging treatment, the mechanical properties of the alloy are greatly improved, and finally the tensile strength, yield strength and elongation are 528MPa, 294MPa and 10.5% respectively.
[0035] 2. The present invention is realized by a semi-continuous casting process. The melt is transported and placed at high and low temperatures to effectively reduce the content of impurity elements in the melt, wherein Fe≤0.0015wt%, Cu≤0.0019wt%, Si≤0.0002wt%, and Ni≤0.0012wt%; the reduction of impurity elements can effectively improve the comprehensive mechanical properties of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The room temperature tensile stress-strain curves of the ultra-high strength deformable magnesium alloys obtained in Example 1 and Comparative Example 1 of the present invention;
[0037] Figure 2 The room temperature tensile stress-strain curve of the ultra-high strength deformable magnesium alloy obtained in Comparative Example 2 of the present invention;
[0038] Figure 3 This is the scanning electron microscope microstructure OM image of Example 1 in the extruded state;
[0039] Figure 4 The OM image of the scanning electron microscope microstructure of Comparative Example 1 in the extruded state;
[0040] Figure 5 This is a SEM image of the microstructure of Example 1 in the extruded state;
[0041] Figure 6 This is a SEM image of the microstructure of Comparative Example 1 in the extruded state;
[0042] Figure 7 This is the SEM image of the microstructure of Comparative Example 2 in the extruded state. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below through specific embodiments:
[0044] Example 1
[0045] 1. Obtain the original ingot with target composition through semi-continuous casting process
[0046] (1) Material preparation: The raw materials of the alloy are pure magnesium ingot (Mg≥99.99wt%), pure zinc ingot (Zn≥99.9wt%), Mg-30Gd master alloy, Mg-5Mn master alloy and Mg-30Y master alloy.
[0047] Prepare the following raw materials by weight percentage:
[0048] Gd (wt%) Y(wt%) Zn (wt%) Mn (wt%) (Mg(wt%) Ingredient Value 10.2 2.1 1 0.45 margin
[0049] (2) Preheating the crucible: During production, set the temperature of the resistance furnace to 600°C and preheat the crucible to dark red.
[0050] (3) Loading: First add pure magnesium ingots several times. After each addition, sprinkle a layer of RJ-6 flux on the surface to prevent oxidation of the melt surface.
[0051] (4) Alloy composition homogenization treatment: Heat to 790℃, remove slag, and then put Mg~30Gd master alloy, Mg~5Mn master alloy, Mg~30Y master alloy and pure zinc ingot into the crucible. Stir manually for 10 minutes, and sprinkle RJ-6 flux evenly on the liquid wave crest during stirring. After stirring, use a slag-cleaning spoon to remove the slag at the bottom and surface of the pot. Finally, sprinkle a thin layer of RJ-6 flux evenly on the surface and let it settle for 10 minutes.
[0052] (5) Refining
[0053] Primary refining: insert the argon tube 100mm above the bottom of the crucible and pull it upwards, adjust the argon flow rate to 0.08MPa in eight equal directions of the crucible diameter, and refine for 5min. During the refining process, continuously sprinkle the refining agent evenly on the liquid wave crest.
[0054] Secondary refining: Argon stirring is also used for 5 minutes, the gas flow rate is 0.08MPa, and the refining agent is continuously and evenly sprinkled on the wave crest during the refining process until the surface of the magnesium melt becomes mirror-like, and then the refining is stopped.
[0055] The refining agent is a mixture of RJ-6 flux and magnesium fluoride in a mass ratio of 4:1. The total amount of the refining agent used in the primary refining and the secondary refining is 2-3% of the total amount of the feed.
[0056] (6) Let stand
[0057] First, high temperature static place is performed, and then low temperature static place is performed; wherein,
[0058] High temperature standing: After refining, scrape off the surface scum, sprinkle a layer of RJ-6 flux to cover, and then transfer to high temperature standing, the temperature is 810℃, and the time is 10min.
[0059] Low temperature standing: After the high temperature standing is completed, turn off the furnace and cool to 700℃ and keep it for 10 minutes to reduce the iron content.
[0060] The total amount of RJ-6 flux used in the charging step (3), the homogenizing step (4) and the standing step (6) is 1% of the total amount of material.
[0061] (7) Semi-continuous casting
[0062] The pot cover with pre-smashed packing is hoisted on the crucible with a crane and aligned with the crucible flange; the casting tube is heated to red and then slowly placed into the crucible and fixed. The crystallizer is blown dry with dry compressed air, the inner wall is brushed with lubricating oil, the casting base is raised 40mm into the crystallizer, and the asbestos rope is plugged in. The tools used for casting are cleaned and fully preheated. During casting, the ratio of sulfur hexafluoride and argon is 1:5, the casting temperature is 720℃, the water temperature is room temperature, the casting speed is 110-130mm / min, the water flow rate is 100-120L / min, the water pressure is 0.15-0.25Mpa, and finally the original ingot of magnesium alloy ingot is cast.
[0063] 2. Two-stage solution treatment: The original ingot obtained by the semi-continuous casting process is subjected to two-stage solution treatment. First, the solution temperature is controlled to 500°C and the solution time is controlled to 8 hours; then the temperature is raised to 520°C and the time is controlled to 12 hours. After completion, it is water-cooled to room temperature.
[0064] 3. Deformation treatment: The sample after double-stage solution treatment was subjected to extrusion deformation treatment, wherein the extrusion temperature was 420°C, the extrusion ratio was 15:1, and then the extruded rod was obtained by air cooling to room temperature.
[0065] 4. Aging treatment: The obtained extruded rod is subjected to aging treatment at 200° C. for 56 hours, and then air-cooled to room temperature to obtain the ultra-high strength deformable magnesium alloy.
[0066] Example 2
[0067] 1. Obtain the original ingot with target composition through semi-continuous casting process
[0068] (1) Material preparation: The raw materials of the alloy are pure magnesium ingot (Mg≥99.99wt%), pure zinc ingot (Zn≥99.9wt%), Mg-30Gd master alloy, Mg-5Mn master alloy and Mg-30Y master alloy.
[0069] Prepare the following raw materials by weight percentage:
[0070] Gd (wt%) Y(wt%) Zn (wt%) Mn (wt%) (Mg(wt%) Ingredient Value 10.2 2.1 1 0.45 margin
[0071] (2) Preheating the crucible: During production, set the temperature of the resistance furnace to 600°C and preheat the crucible to dark red.
[0072] (3) Loading: First add pure magnesium ingots several times. After each addition, sprinkle a layer of RJ-6 flux on the surface to prevent oxidation of the melt surface.
[0073] (4) Alloy composition homogenization treatment: Heat to 790℃, remove slag, and then put Mg~30Gd master alloy, Mg~5Mn master alloy, Mg~30Y master alloy and pure zinc ingot into the crucible. Stir manually for 10 minutes, and sprinkle RJ-6 flux evenly on the liquid wave crest during stirring. After stirring, use a slag-cleaning spoon to remove the slag at the bottom and surface of the pot. Finally, sprinkle a thin layer of RJ-6 flux evenly on the surface and let it settle for 10 minutes.
[0074] (5) Refining
[0075] Primary refining: insert the argon tube 100mm above the bottom of the crucible and pull it upwards, adjust the argon flow rate to 0.08MPa in eight equal directions of the crucible diameter, and refine for 5min. During the refining process, continuously sprinkle the refining agent evenly on the liquid wave crest.
[0076] Secondary refining: Argon stirring is also used for 5 minutes, the gas flow rate is 0.08MPa, and the refining agent is continuously and evenly sprinkled on the wave crest during the refining process until the surface of the magnesium melt becomes mirror-like, and then the refining is stopped.
[0077] The refining agent is a mixture of RJ-6 flux and magnesium fluoride in a mass ratio of 4:1. The total amount of the refining agent used in the primary refining and the secondary refining is 2-3% of the total amount of the feed.
[0078] (6) Let stand
[0079] First, high temperature static place is performed, and then low temperature static place is performed; wherein,
[0080] High temperature standing: After refining, scrape off the surface scum, sprinkle a layer of RJ-6 flux to cover, and then transfer to high temperature standing, the temperature is 810℃, and the time is 10min.
[0081] Low temperature standing: After the high temperature standing is completed, turn off the furnace and cool to 700℃ and keep it for 10 minutes to reduce the iron content.
[0082] The total amount of RJ-6 flux used in the charging step (3), the homogenizing step (4) and the standing step (6) is 1% of the total amount of material.
[0083] (7) Semi-continuous casting
[0084] The pot cover with pre-smashed packing is hoisted on the crucible with a crane and aligned with the crucible flange; after heating the casting tube to red, slowly put it into the crucible and fix it. The crystallizer is blown dry with dry compressed air, the inner wall is brushed with lubricating oil, the casting base is raised 40mm into the crystallizer, and the asbestos rope is plugged in. The tools used for casting are cleaned and fully preheated. During casting, the ratio of sulfur hexafluoride and argon is 1:5, the casting temperature is 710-730℃, the water temperature is room temperature, the casting speed is 110-130mm / min, the water flow rate is 100-120L / min, the water pressure is 0.15-0.25Mpa, and finally the original ingot of magnesium alloy ingot is cast.
[0085] 2. Two-stage solution treatment: The original ingot obtained by the semi-continuous casting process is subjected to two-stage solution treatment. First, the solution temperature is controlled to 500°C and the solution time is controlled to 6 hours; then the temperature is raised to 540°C and the time is controlled to 10 hours. After completion, it is water-cooled to room temperature.
[0086] 3. Deformation treatment: The sample after double-stage solution treatment was subjected to extrusion deformation treatment, wherein the extrusion temperature was 440°C and the extrusion ratio was 15:1, and then the extruded rod was obtained by air cooling to room temperature.
[0087] 4. Aging treatment: The obtained extruded rod is subjected to aging treatment at 200° C. for 48 hours, and then air-cooled to room temperature to obtain the ultra-high strength deformable magnesium alloy.
[0088] Comparative Example 1
[0089] The difference from Example 1 is that the semi-continuous casting process to obtain the original ingot of target composition is replaced by the traditional gravity casting process to obtain the original ingot of target composition.
[0090] Specifically, the steps of the traditional gravity casting process are as follows:
[0091] (1) Ingredients: the same as those in Example 1;
[0092] (2) Melting: coating the inner wall of a steel crucible with hexagonal boron nitride, preheating and drying the crucible at 200°C, then placing a high-purity magnesium ingot into the crucible and placing it in a melting furnace, setting the temperature of the melting furnace to 710°C, and introducing a mixed gas of carbon dioxide and sulfur hexafluoride in a volume ratio of 5:1 for protection; after the pure magnesium ingot is melted, raising the temperature to 720°C, adding a pure zinc ingot, Mg-30Gd master alloy, Mg-30Y master alloy and Mg-5Mn master alloy into the crucible; after all are melted, stirring the melt to make the alloy composition uniform;
[0093] (3) Refining: Keep the melt temperature at 720°C, remove the scum on the melt surface, add refining agent RJ-6 (the amount added is 0.5-1% of the melt mass) to the melt, and then stir it thoroughly;
[0094] (4) Standing: The melt temperature was maintained at 720°C and then stood for 30 min. The melt was then water-cooled to obtain an original alloy ingot.
[0095] Comparative Example 2
[0096] The only difference from Example 1 is that the Zr element is replaced by the Mn element.
[0097] During the experiment, it was found that the room temperature mechanical properties of the ultra-high strength deformable magnesium alloy prepared in Example 1 were optimal, and Example 1 was the optimal example.
[0098] The room temperature mechanical properties of the ultra-high strength wrought magnesium alloys prepared in Example 1, Comparative Example 1 and Comparative Example 2 are tested, as shown in Table 1.
[0099] Table 1
[0100]
[0101] It should be noted that the extruded state in Table 1 is the state of the extruded rod obtained after the deformation treatment step; the extrusion + heat treatment state is the state of the ultra-high strength deformed magnesium alloy obtained after the aging treatment step.
[0102] It can be seen from Table 1 that Example 1 has better mechanical properties than Comparative Example 1. The mechanical properties of the extruded rod obtained in Example 1 after the deformation treatment step reached a tensile strength of 439MPa, a yield strength of 290MPa, and an elongation of 14.1%; the mechanical properties of the ultra-high strength deformed magnesium alloy obtained after the aging treatment step reached a tensile strength of 528MPa, a yield strength of 294MPa, and an elongation of 10.1%. In Comparative Example 1, a higher elongation of 20.8% was shown in the extruded state. After the aging treatment step, the yield strength of the alloy in Comparative Example 1 increased by 70MPa, which is a greater improvement than the yield strength of Example 1.
[0103] according to Figures 3 to 6The recrystallized grains and deformed grains of the alloy after deformation are clearly shown. After extrusion, the LPSO phase at the grain boundary is torn, bent, twisted and broken. The particle induction (PSN) mechanism further promotes recrystallization while also pinning the grain boundary, inhibiting the growth of recrystallized grains. The solid solubility of the Mn element in the magnesium matrix is low. The Mn element in the alloy usually exists in the form of α-Mn, which has a good inhibitory effect on the growth of the grain boundary, thereby achieving the effect of grain refinement. The deformed magnesium alloy obtained in Example 1 is obtained by semi-continuous casting. Compared with the deformed magnesium alloy obtained by conventional gravity casting in Comparative Example 1, semi-continuous casting can obtain a faster cooling rate, further refine the grains of the alloy, and thus improve the comprehensive mechanical properties of the alloy.
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an ultra-high strength deformable magnesium alloy, characterized in that: The following steps are involved: A Mg-Gd-Y-Zn-Mn alloy is obtained by a semi-continuous casting process; The Mg-Gd-Y-Zn-Mn alloy was subjected to a double-stage high-temperature solution treatment to obtain a sample, and the sample was water-cooled to room temperature; The sample is subjected to extrusion deformation treatment to obtain an extruded rod, and the extruded rod is subjected to air cooling treatment to room temperature; The extruded bars are subjected to aging treatment and then air-cooled to room temperature.
2. The method for preparing an ultra-high strength deformable magnesium alloy according to claim 1, characterized in that: The semi-continuous casting process specifically comprises the following steps: Preheat the crucible: set the resistance furnace temperature to 550-600°C; Furnace loading: first add pure magnesium ingots several times, and sprinkle a layer of RJ-6 flux on the surface after adding pure magnesium ingots each time; Alloy composition homogenization treatment: raise the temperature of the resistance furnace to 770-790℃, scrape off the scum on the liquid surface, then add Mg-30Gd master alloy, Mg-5Mn master alloy, Mg-30Y master alloy and pure zinc ingot into the crucible, stir and sprinkle RJ-6 flux evenly, clean the scum on the bottom and surface of the pot after stirring, and let it settle for 5-10 minutes; Refining: Insert the argon tube 80-100mm above the bottom of the crucible and pass argon in all directions, with a flow rate of 0.03-0.08MPa. Refine for 10-20min. After refining, scrape off the surface scum, sprinkle a layer of RJ-6 flux on it, and then perform high-temperature and low-temperature standing in turn; Semi-continuous casting: Semi-continuous casting is carried out under the protection of sulfur hexafluoride and argon in a volume ratio of 1:
5. After drying the inside of the crystallizer, lubricating oil is brushed on its inner wall, and the casting temperature is controlled to be 710-730°C, the water temperature is room temperature, the casting speed is 110-130mm / min, the water flow rate is 100-120L / min, and the water pressure is 0.15-0.25Mpa.
3. The method for preparing an ultra-high strength deformable magnesium alloy according to claim 2, characterized in that: The high-temperature standing is standing at a temperature of 780 to 810° C. for 10 to 20 minutes; the low-temperature standing is standing at a temperature of 670 to 700° C. for 10 to 20 minutes.
4. The method for preparing an ultra-high strength deformable magnesium alloy according to claim 2, characterized in that: The refining is performed in sequence by performing primary refining and secondary refining; wherein: The primary refining comprises: inserting an argon tube 80 to 100 mm above the bottom of the crucible and pulling it upward, adjusting the argon flow rate to 0.03 to 0.08 MPa in eight equal directions of the crucible diameter, refining for 5 to 10 minutes, and continuously and evenly spreading the refining agent on the wave crest during the refining process; The secondary refining is as follows: argon is used for stirring for 5 to 10 minutes, the gas flow rate is 0.03 to 0.08 MPa, and the refining agent is continuously and evenly sprinkled on the wave crest during the refining process until the surface of the magnesium melt becomes mirror-like, and the refining is stopped; The total amount of refining agent used in the primary refining and the secondary refining is 2-3% of the total amount of raw materials.
5. The method for preparing an ultra-high strength deformable magnesium alloy according to claim 4, characterized in that: The refining agent includes RJ-6 flux and magnesium fluoride, wherein the mass ratio of RJ-6 flux to magnesium fluoride is 4:
1.
6. The method for preparing an ultra-high strength deformable magnesium alloy according to claim 1, characterized in that: The two-stage high temperature solution treatment is specifically: First, the solution is carried out at a solution temperature of 480-500°C for 6-10 hours, and then the temperature is raised to 520-540°C and the solution is carried out for 10-14 hours.
7. The method for preparing an ultra-high strength deformable magnesium alloy according to claim 1, characterized in that: The extrusion temperature in the extrusion deformation process is 400-450° C., and the extrusion ratio is 14-16:
1.
8. The method for preparing an ultra-high strength deformable magnesium alloy according to claim 1, characterized in that: The aging temperature in the aging treatment is 190-210° C., and the aging time is 36-64 hours.
9. An ultra-high strength deformable magnesium alloy, characterized in that: The alloy is prepared by the method for preparing an ultra-high strength deformable magnesium alloy according to any one of claims 1 to 9.
10. The ultra-high strength deformable magnesium alloy according to claim 9, characterized in that: The mass percentages of the components are: Gd 9.5%~10.5%; Y 1.5%~2.5%; Zn 1%~1.5%; Mn 0.5%~0.8%; The remainder is Mg and other irremovable impurity elements.